2021
DOI: 10.3389/fnut.2021.760985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Vitamins and Carotenoids With Liver Steatosis and Fibrosis Detected by Transient Elastography in Adults

Abstract: Background: Vitamins and carotenoids may be involved in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Previously related publications mainly focused on vitamin D and vitamin E, and studies on other vitamins and carotenoids and NAFLD are scarce.Methods: This study aimed to explore the clinical relevance of vitamin A, B vitamins (vitamin B1, vitamin B2, niacin, vitamin B6, folate, vitamin B12, and choline), vitamin C and carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, lutein + ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Second, we excluded participants with age of DM onset of < 30 years of age to minimize the number of participants with T1DM, as previously described [ 26 , 27 ], as the NHANES database does not differentiate diabetes by type. Third, the values of CAP defining hepatic steatosis and LSM defining significant fibrosis are both inconsistent among different studies using NAHENS 2017–2018 database [ 13 , 28 , 29 ]. Thus, the sensitivity and specificity of TE test may vary depending on the cut-off values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we excluded participants with age of DM onset of < 30 years of age to minimize the number of participants with T1DM, as previously described [ 26 , 27 ], as the NHANES database does not differentiate diabetes by type. Third, the values of CAP defining hepatic steatosis and LSM defining significant fibrosis are both inconsistent among different studies using NAHENS 2017–2018 database [ 13 , 28 , 29 ]. Thus, the sensitivity and specificity of TE test may vary depending on the cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure for our study is the T2DM status, defined according to the following criteria: participants being informed that they had DM by their doctor, age at time of DM diagnosis ≥ 30 years; and/or a HbA1c level ≥ 6.5% [ 11 ]. Outcomes on liver ultrasound TE were measured using a FibroScan® system (model 502, V2 Touch) and included CAP, with a value ≥ 274 dB/m indicative of liver steatosis [ 12 ], and LSM, with a median value ≥ 8 kPa indicative of significant fibrosis [ 13 ], provided by the liver ultrasound TE on a FibroScan® model 502 V2 Touch equipped with a medium or extra large probe. The following demographic and clinical variables were also collected as covariates in our analyses: age; sex; race; level of education; ratio of family income to poverty; level of moderate recreational activities; history of smoking ≥ 100 cigarettes; BMI; and blood urea nitrogen (BUN) levels, total cholesterol, uric acid, gamma-glutamyl transpeptidase (GGT), aspartic acid transferase, alanine amino transferase (ALT), alkaline phosphatase (ALP), and serum glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Although liver biopsy is still the gold standard for diagnosing and assessing the severity of liver steatosis and NASH, other non-invasive and cost-effective procedures have been extensively researched and reported [ 15 ]. Transient elastography (TE) is regarded as a promising and regularly used non-invasive approach for liver steatosis and fibrosis quantification [ 16 ] and has been utilized to identify liver steatosis and fibrosis in the general population [ 17 , 18 ]. The controlled attenuation parameter (CAP) value, in particular, rises with the degree of liver steatosis and can be applied to detect steatosis of more than 5% [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al ( 27 ) found that the risk of NAFLD was decreased by 0.71 times in the highest quartile of dietary vitamin C intake compared with the lowest quartile, which was similar to our findings. More and more epidemiologic studies proposed that serum VC levels had a significant negative correlation with hepatic steatosis and hepatic fibrosis ( 28 , 29 ). According to a prospective double-blinded randomized controlled trial, oral VC supplements could significantly improve liver function and glucose metabolism as well as guarantee intestinal microbial diversity and adiponectin concentration for patients with NAFLD ( 30 ).…”
Section: Discussionmentioning
confidence: 99%